Modern Pedagogical Technologies and Leading International Practices in Developing Students’ Reflective Thinking - Abdullayeva Ziroatxon Qurbonovna (International Scientific and Current Research Conferences, 2025)
The article analyzes the theoretical and practical foundations of applying modern pedagogical technologies in shaping students’ reflective thinking. It also examines leading practices for developing reflection skills in foreign countries and proposes ways to adapt them to Uzbekistan’s higher education system.